The Influence of Service Quality, Marketing Mix, and Trust on Customer Satisfaction among KUR Loan Customers at PT Bank Negara Indonesia (Persero) Tbk Tanjungpinang Branch - Qorina Amalia; Putu Indah Rahmawati; Ni Luh Wayan Sayang Telagawathi (International Journal of Management Science and Information Technology, 2026)
This study examines the influence of service quality, marketing mix, and trust on customer satisfaction among Kredit Usaha Rakyat (KUR) customers at PT Bank Negara Indonesia (Persero) Tbk, Tanjungpinang Branch. The research was motivated by a substantial decline in the number of KUR customers between 2022 and 2024, indicating potential challenges in maintaining customer satisfaction within the banking sector. Understanding the factors that shape customer satisfaction is essential for improving service performance and strengthening customer relationships, particularly in government-supported financing programs. A quantitative research design was employed using a survey method. Data were collected from 91 KUR customers through structured questionnaires measured on a Likert scale. The collected data were analyzed using multiple linear regression, supported by validity testing, reliability testing, classical assumption testing, t-tests, F-tests, and coefficient of determination analysis using SPSS 23. The findings reveal that service quality has a positive and significant effect on customer satisfaction (t = 6.095, p < 0.001). Similarly, the marketing mix significantly influences customer satisfaction (t = 5.027, p < 0.001), while trust also demonstrates a positive and significant effect (t = 2.363, p = 0.020). Furthermore, service quality, marketing mix, and trust jointly exert a significant influence on customer satisfaction (F = 188.818, p < 0.001). The model explains 86.2% of the variance in customer satisfaction. These findings highlight the strategic importance of delivering superior service quality, implementing effective marketing mix strategies, and fostering customer trust to enhance satisfaction and sustain the competitiveness of KUR banking services.